A Cooperative Function with Cloud Communication for Avoiding Collisions with Occluded Pedestrians - Concept Development and Feasibility Evaluation - Stolt, Caroline; Fahlin Strömberg, Jeanna (My University, 2017)
Annually, there are 1.25 million fatalities in traffic accidents around the world. In EU, 21 % of the road fatalities are pedestrians. Without action, road traffic crashes are predicted to be the 7th leading death cause by 2030. The safety of vehicles have improved over the past decades, during which, traditionally the focus has been on passive safety, reducing the injuries from a collision. During the last decade, however, active safety which focuses on preventing or mitigating collisions, have become increasingly important. Active safety functions, such as collision warning and avoidance systems, are common features in today’s vehicles. However, in several common scenarios, today’s active safety systems are not enough to avoid or mitigate a collision. The aim of the thesis was to develop a concept of a cooperative active safety function which avoids or mitigates a collision between an occluded pedestrian and a following vehicle whose view is compromised by a vehicle in the adjacent lane. Within this thesis, we establish the potential benefit, limitations and feasibility of such function by extending existing active safety systems with cloud communication. In this thesis, a concept of an occluded pedestrian warning and collision avoidance function was developed and evaluated in simulation. The function is cooperative and utilizes sensors in the occluding and following vehicle as well as cloud communication between them. The simulation was conducted in an ideal simulation environment with and without communication latency as well as in a cloud test bench. The developed concept yielded a large benefit for a wide set of parameter combinations and even for long latency of several hundred ms. Nevertheless, latency proved to be a limitation and should be limited to 100-200 ms considering the uncertainties. To conclude, a benefit for our cooperative function was shown for a wide range of parameters and scenarios. Long latencies limit the effectiveness of such system but benefit can still be observed. The current function can yield benefits for the type of scenarios which were tested. With soon expected technology shifts, the benefit of our function in more complex scenarios would increase.
Keywords: Informations- och kommunikationsteknik; Transport; Elektroteknik och elektronik; Information & Communication Technology; Transport; Electrical Engineering, Electronic Engineering, Information Engineering